A Multifunctional Photoacoustic/Fluorescence Dual‐Mode‐Imaging Gold‐Based Theranostic Nanoformulation without External Laser Limitations. Issue 19 (6th April 2022) - Zhang, Junfeng; Yin, Xiaofeng; Li, Chenchen; Yin, Xuelian; Xue, Qianghua; Ding, Lin; Ju, Jiale; Ma, Jifei; Zhu, Ying; Du, Dongshu; Reis, Rui L.; Wang,, Yanli
Abstract: Theranostics is a new type of biomedical technology that organically combines the diagnosis and therapy of diseases. Among molecular imaging techniques, the integration of photoacoustic (PA) and fluorescence (FL) imaging modes with high sensitivity and imaging depth provides precise diagnostic outcomes. Gold nanorods (Au NRs) are well‐known contrast agents for PA imaging and photothermal therapy. However, their high toxicity, poor biocompatibility, rapid clearance, and the need for an external laser source limit their application. Therefore, modification of Au NRs with carbon‐based nanomaterials (CBNs) is done to obtain a multifunctional dual‐mode gold‐based nanoformulation (mdGC), which preforms dual‐mode imaging of PA and FL. The results show that mdGC promotes tumor cell apoptosis and exhibits good antitumor performance through the mitochondria‐mediated apoptotic pathway by increasing the production of intracellular reactive oxygen species, reducing mitochondrial membrane potential, and regulating the expression of apoptosis‐related genes. The targeting rate of mdGC to tumor tissue is up to 20.71 ± 1.94% ID g ‐1 ; the tumor growth inhibition rate is as high as 80.44% without external laser sources. In general, mdGC is a potential multifunctional diagnostic and therapy integrated nanoformulation. Abstract : mdGC as a multifunctional photoacoustic/fluorescence dual‐mode imaging theranostic nanoformulation shows good diagnosis and treatment performance without external laser limitations through the mitochondria‐mediated apoptotic pathway by increasing the production of intracellular reactive oxygen species, reducing the mitochondrial membrane potential, and regulating the expression of apoptosis‐related genes.